ASSESSMENT OF GROUND SURFACE DEFORMATION IN BENGKULU CITY INDUCED BY EARTHQUAKES USING DINSAR-BASED REMOTE SENSING IMAGE ANALYSIS - Ferzha Putra Utama; Arie Vatresia; Lindung Zalbuin Mase; Ahmad Faris (International Journal of Remote Sensing and Earth Sciences, 2024)
In 2007, Bengkulu city, Indonesia and its surrounding areas experienced a significant earthquake with a magnitude of 8.6 Mw, resulting in extensive damage. Between 2014 and 2022, Bengkulu Province encountered a total of 3469 earthquakes, signifying a heightened frequency of seismic activity in the region. This escalated seismic activity in Bengkulu elicits concerns regarding potential ground surface deformation. To address this, the study utilized DInSAR (Differential Interferometry SAR) technology, employing a blend of satellite images to quantify land surface deformation. Notably, the research made use of three pairs of satellite images for analysis. One pair of ALOS-PALSAR images dated between January 29 and September 16, 2007, was employed to investigate ground surface deformation following the September 12, 2007 earthquake. Additionally, observations were made using two pairs of Sentinel-1 satellite images covering periods from November 3 to 27, 2014, and from June 30 to July 24, 2022, to monitor land surface deformation resulting from earthquakes on November 10, 2014 and July 20, 2022. The study findings depicted uplift deformation reaching 53.4 mm and the highest subsidence measuring -12.8 mm in the ALOS-PALSAR image pair. In the Sentinel-1 image pair between November 3 and 27, 2014, the most notable observed uplift amounted to 38.9 mm, while the greatest subsidence was recorded at -34.8 mm. Lastly, the image pair dated between June 30 and July 24, 2022, exclusively exhibited uplift, with values peaking at 45.2 mm.